Appel Is Forever : A Child's Memoir - Whiteley, Suzanne Mehler, 1935- (Book collections on Project MUSE., 1999)
The author describes her experiences during the Holocaust between the ages of five and nine, in Amsterdam, as a prisoner in the Westerbork and Bergen-Belsen concentration camps, and eventually in the United States.